Potentials of Sago Fibre Hydrolysate (SFH) as the Sole Fermentation Medium for Production of Bioethanol - Sharifah, Mohammad (Universiti Malaysia Sarawak (UNIMAS), 2018)
Sago waste water which contains starchy fibres from sago starch processing mills conunonly discharged directly to nearby stream thus contribute to serious environmental pollution. This study is an effort to utilize residual starch trapped in sago fibres as raw materials for bioethanol production, hence could minimize the amount of sago wastes. Sago fibre (SF) was utilized into Sago Fibre Hydrolysate (SFH) via enzymatic hydrolysis using commercial enzymes; Liquozyme SC DS and Spirizyme Fuel HS. The load of Sago Fibre Powder (SFP) at 7% (w/v) was used for the hydrolysis process. Lower glucose concentration (46.24 ± 2.27 giL) was obtained, thus, an alternative method (cycles I, II, and III) which involved reusing the hydrolysate for subsequent enzymatic hydrolysis cycles was adopted. Greater improvement of higher glucose concentration (149.36 ± 1.53 giL) was achieved after completing cycle III of the hydrolysis process. Glucose (92%) was found to be the highest monomeric sugar component in the hydrolysate, followed by cellobiose (3%), and other oligosaccharides (5%). This study confirmed that 50 giL glucose from SFH media (without addition ofnitrogen source) capable of generating maximum ethanol concentration at 20.33 ± 0.15 giL, during 24 hrs of fermentation. Similar concentration ofbioethanol was obtained in 50 giL glucose ofCGmedia (without addition of nitrogen source) which is at 20.04 ± 0.06 giL. When SFH amended with YE, ethanol concentration was slightly higher (22.7 1 ± 0.31 giL), by 2.38 giL or 10.5%. However, ethanol concentration was much higher in SFH amended with Peptone (P) at 24.02 ± 0.01 giL, whereas 0.50 ± 0.002 gig of ethanol yield was generated. Thus, 97.16 ± 0.402% of fermentation efficiency was achieved during 24 hours offermentation. In this study, ammonium sulfate, peptone and urea were found to be feasible as nitrogen source in bioethanol production by using CBY. Based on statistical analysis, ammonium sulfate (AS) was the best nitrogen source, give the highest ethanol yield (0.50 ± 0.002 gig) and highest fennentation efficiency in converting glucose to ethanol (98.58 ± 0.449%), followed by peptone (0.50 ± 0.002 gig), with fennentation efficiency of 97.16 ± 0.402%, and urea (0.49 ± 0.002 gig), with 96.34 ± 0.406% of fennentation efficiency. Conclusively, the glucose in sago fibre hydrolysate (SFH) was metabolized efficiently by CBY during ethanol fennentation, thus exhibits the capability ofSFH to be an alternative substrate with less expensive nitrogen source for the renewable bioethanol production